2008
DOI: 10.1086/587932
|View full text |Cite
|
Sign up to set email alerts
|

On the Nature of Seyfert Galaxies with High [Oiii] λ5007 Blueshifts

Abstract: We have studied the properties of Seyfert galaxies with high [OIII]5007 blueshifts ("blue outliers"), originally identified because of their strong deviation from the M BH − σ relation of normal, narrowline Seyfert 1 (NLS1) and broad-line Seyfert 1 (BLS1) galaxies. These blue outliers turn out to be important test-beds for models of the narrow-line region (NLR), for mechanisms of driving large-scale outflows, for links between NLS1 galaxies and radio galaxies, and for orientation-dependent NLS1 models. We repo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
292
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(332 citation statements)
references
References 142 publications
38
292
2
Order By: Relevance
“…Previous studies frequently identified a strong correlation between the [O iii] line widths and the [O iii] blueshifts (e.g., Bian et al 2005;Komossa et al 2008;Zamanov et al 2002). The correlation is commonly explained by the material outflows.…”
Section: Line Shape Parameters ξ 3 and ξmentioning
confidence: 95%
See 3 more Smart Citations
“…Previous studies frequently identified a strong correlation between the [O iii] line widths and the [O iii] blueshifts (e.g., Bian et al 2005;Komossa et al 2008;Zamanov et al 2002). The correlation is commonly explained by the material outflows.…”
Section: Line Shape Parameters ξ 3 and ξmentioning
confidence: 95%
“…The bulk relative velocity shift of the [O iii] emission line is measured relative to the Hβ emission line in each emission-lineisolated spectrum, because the Hβ line can be easily detected and because the line shows a very small velocity shift relative to the galaxy rest frame (e.g., Komossa et al 2008). The velocity shift is calculated as Δυ = δλ/λ 0 c, where λ 0 and c are the rest-frame wavelength of the [O iii] λ5007 emission line and the velocity of light, respectively.…”
Section: Relative Velocity Shiftsmentioning
confidence: 99%
See 2 more Smart Citations
“…The [O III] λ4959 profile is much broader than the CO profile, FWHM = 2200 ± 180 km s −1 , with a single identifiable peak. Such broad line profiles are commonly interpreted as gas stirred up and accelerated by the AGN in the inner narrowline region (e.g., Komossa et al 2008). This line probes warm ionized gas that is highly excited, but low in mass, unlike the CO lines.…”
Section: Gas Dynamicsmentioning
confidence: 99%